The Potential of Digital Media: Theoretical Observations on the Educational and Didactic Potential of Tablets - And a Conceptual Outline of Using Them in Schools - Thomas Knaus (New Zealand Journal of Teachers' Work)
When tablets are used in schools for internet research and in passive reception processes only, a huge potential of digital media remains unexploited. By referring to an interactionist-constructivist model of learning, requirements for sustainable and motivating learning can be identified, which take into account the findings of psychology of learning and educational theory. In an exemplary analysis of two media for instruction, the exercise book and tablet, these criteria are assessed from a communication studies perspective: by comparing these both media, two conceptual potentials of using digital media in schools can be exemplarily detected.